Effects of prohormone supplementation in humans: A review - Ziegenfuss, T. N.; Berardi, J. M.; Lowery, L. M.; Antonio, J. (Canadian Journal of Applied Physiology, 2002)
Despite a relative dearth of information on their effects, supplementation with prohormones has become a popular practice. Unlike synthetic anabolic-androgenic steroids, many of these over-the-counter androgens are produced endogenously by adrenal, gonadal and peripheral steroidogenic pathways as part of the normal sexual and reproductive hormonal milieu. It has been contended that peripheral enzymatic conversion of these prohormones to testosterone or nortestosterone (via ingestion of androstenedione/androstenediol or 19-nor-androstenedione/androstenediol, respectively) might lead to anabolic and/or ergogenic effects. Existing data suggest that acute oral ingestion of ³ 200 mg androstenedione or androstenediol modestly and transiently increases serum testosterone concentrations in men; however, this is accompanied by greater increases in circulating estrogen(s). At doses < 300 mg/d, oral supplementation for as long as 12-weeks with androstenedione or androstenediol has no effect on body composition or physical performance and decreases high-density lipoprotein cholesterol. Similarly, oral supplementation with norandrostenedione and norandrostenediol for up to eight weeks has no effect on body composition or physical performance. In light of these data, new products have been developed that use alternative modes of prohormone administration (sublingual/transbuccal and cyclodextrin-complexation). Future studies should critically examine the effects of these approaches. However, within the framework of the research reviewed, over-the-counter oral prohormone supplementation is ineffective at increasing muscle mass or athletic performance. As a result of the potential health concerns that have been raised, the risk to benefit ratio of using these substances orally seems unfavorable.